Short communication. Viability and pathogenicity of Ascosphaera apis preserved in integral rice cultures - Palacio, M.A.=700 1 Peña, N.; Clemente, G.; Ruffinengo, S.
Es, En)
Ilus., 34 ref.
Keywords: APIS MELLIFERA; COMPORTAMIENTO; MICOSIS; ASCODPHAERA APIS; INOCULACION; LARVAS; MEDIO DE CULTIVO; ESPAÑA; CRIA YESIFICADA